2019
DOI: 10.1111/psyg.12454
|View full text |Cite
|
Sign up to set email alerts
|

Meaning and practices of spiritual care for older people with dementia: experiences of nurses and care workers

Abstract: Background:The aim of the present study was to comprehensively investigate the meaning and practices of spiritual care for older people with dementia based on the perspective and experiences of nurses and care workers. Methods: The study was designed according to qualitative research strategies and used face-to-face interview data, with a focus on the experiences of nurses and care workers who care for elderly persons with dementia. Five nurses and 13 care workers from nine care facilities participated. We con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…If there is a longing for something else or past when living in a nursing home, this can be a challenge, representing itself in a struggle to adapt to the new life situation. Such residents are more likely to not feel at‐home and their struggles can be identified as low spiritual well‐being or be perceived as spiritual suffering (Bergbom et al, 2021; Hirakawa, 2014). When participants expressed a lack of purpose or meaning in life, this was reflected in our findings as low well‐being scores.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If there is a longing for something else or past when living in a nursing home, this can be a challenge, representing itself in a struggle to adapt to the new life situation. Such residents are more likely to not feel at‐home and their struggles can be identified as low spiritual well‐being or be perceived as spiritual suffering (Bergbom et al, 2021; Hirakawa, 2014). When participants expressed a lack of purpose or meaning in life, this was reflected in our findings as low well‐being scores.…”
Section: Discussionmentioning
confidence: 99%
“…Although there is no consensus on a definition for spiritual suffering, suffering on a spiritual level is still recognised, especially in palliation (Bahrain et al, 2019). Spiritual suffering can be described as related to anxiety for the future and loss of meaning and sense of worth (Hirakawa, 2014). The core of compassionate care based on Eriksson's theory is care which is directed towards the alleviation of suffering in the other human beings (Bergbom et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Because studies reported their results generally, it seemed like both types of subjects benefited from the Paro intervention, particularly for those with advanced dementia (Takayanagi et al., 2014). Researchers were more willing to explore the roles of Paro for the older adults with intensive need of spiritual and emotional care, such as older adults with cognitive impairment or disability due to their poor ability to control their behavior and emotions and these kinds of older adults cannot express their own spiritual needs effectively (Hirakawa et al., 2020), even though Paro was designed to improve positive feelings for all individuals (McGlynn et al., 2017). However, in a quasi‐experimental study (Bemelmans et al., 2015), researchers using Paro in intramural care as the intervention method found that therapeutic outcomes had no relationships with dementia severity.…”
Section: Discussionmentioning
confidence: 99%
“…Recognition of the patient's spiritual needs among coexisting physical, social, and emotional needs requires the involvement and collaboration of all care providers [4,7,22,27,28]. Understanding the patient's spirituality is an integral part of care [12], ring to the patients' life achievements and manifesting active listening as a communication strategy [43].…”
Section: Discussionmentioning
confidence: 99%